SURVEY BALANCE ABILITY IN STROKE PATIENTS AT THONG NHAT GENERAL HOSPITAL IN DONGNAI PROVINCE. (Vietnam Journal of Community Medicine, 2026)
Balance function plays an important role in a person's movement and mobility. In stroke patients, balance function is affected to different degrees. Therefore, accurate assessment will help to have a suitable intervention plan, especially rehabilitation. Objective: To survey balance ability in stroke patients at the Department of Neurology, Thong Nhat General Hospital Dong Nai province in 2024. Method: Cross-sectional descriptive study design. Including 102 patients who met the selection criteria for the study. Convenient sampling method. Results: The average age was 59.97 ± 10.98, with the highest number in the 56-65 age group (27.8%). The rate of patients with high blood pressure was the highest at 67%, and the history of osteoarthritis was 47.4%. When evaluated by the Berg scale, the Berg scale score in women was higher than that in men at 31.50 ± 9.54 and 29.29 ± 10.44, respectively, and the rate of patients at high risk of falling was 27.8%. This score was quite high, reflecting low balance function. Conclusion: The survey results showed that the rate of stroke patients with impaired balance function was quite high. Therefore, a good management plan and appropriate physical therapy exercises were proposed for each patient.
Keywords: balance, stroke